A comparative study of phosphoric acid‐doped m‐PBI membranes. Issue 1 (31st October 2013) - A. Perry, Kelly; L. More, Karren; Andrew Payzant, E.; Meisner, Roberta A.; Sumpter, Bobby G.; Benicewicz, Brian C.
ABSTRACT Phosphoric acid (PA)‐doped m‐polybenzimidazole (PBI) membranes used in high temperature fuel cells and hydrogen pumps were prepared by a conventional imbibing process and a sol–gel fabrication process. A comparative study was conducted to investigate the critical properties of PA doping levels, ionic conductivities, mechanical properties, and molecular ordering. This systematic study found that sol–gel PA‐doped m‐PBI membranes were able to absorb higher acid doping levels and to achieve higher ionic conductivities than conventionally imbibed membranes when treated in an equivalent manner. Even at similar acid loadings, the sol–gel membranes exhibited higher ionic conductivities. Heat treatment of conventionally imbibed membranes with ≤29 wt % solids caused a significant reduction in mechanical properties; conversely, sol–gel membranes exhibited an enhancement in mechanical properties. From X‐ray structural studies and atomistic simulations, both conventionally imbibed and sol–gel membranes exhibited d‐spacings of 3.5 and 4.6 Å, which were tentatively attributed to parallel ring stacking and staggered side‐to‐side packing, respectively, of the imidazole rings in these aromatic heterocyclic polymers. An anisotropic staggered side‐to‐side chain packing present in the conventional membranes may be related to the reduction in mechanical properties. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Polym. Phys. 2014, 52, 26–35